The Influence of algorithms and Monetization Features on Revenue Structure in the Global Creator Economy (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
The digital transformation has given rise to the creator economy, an ecosystem where individuals monetize their creativity through digital platforms. This systematic literature review examines the interplay between platform algorithms and monetization features in shaping creator revenue structures. employing a systematic literature review methodology, this study synthesizes research published between 2013 and 2025 from major academic databases. Findings reveal that platform algorithms function as digital gatekeepers, creating visibility inequality among creators, while diverse monetization features enable multiple revenue streams. The interaction between algorithmic visibility and monetization mechanisms produces complex and often inequitable revenue distributions. Strategic content adaptation and revenue diversification emerge as critical survival strategies for creators. The study concludes that transparency in algorithmic processes and equitable revenue-sharing models are essential for sustainable creator economy ecosystems. This research contributes to understanding the structural dynamics of digital creative labor and informs policy development for platform governance.
Keywords: creator economy; digital platforms; monetization; platform algorithms; revenue structure